2022
DOI: 10.1111/soc4.13021
|View full text |Cite
|
Sign up to set email alerts
|

Parenting young adults across social class: A review and synthesis

Abstract: Research on parental involvement has traditionally focused on social class differences in parenting behavior throughout early childhood and K‐12 schooling. Yet there is mounting evidence that similar class divides persist as children exit high school and progress through young adulthood. This review examines parents' roles in young adults' lives, focusing on class differences in non‐financial forms of involvement. These processes are often hidden from public view and have received less attention in prior revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 163 publications
(207 reference statements)
0
6
0
Order By: Relevance
“…These findings are particularly relevant to scholarship on parent/young adult coresidence. Despite much scholarly attention to this phenomenon in recent decades (for a review, see Mazurik et al, 2020), we still know relatively little about how the qualitative experience of coresidence varies across social class (van Stee, 2022). Addressing this gap, the present study revealed dramatic differences in young adults' family roles and learning environments.…”
Section: Implications For Inequality During the Covid-19 Pandemicmentioning
confidence: 65%
See 1 more Smart Citation
“…These findings are particularly relevant to scholarship on parent/young adult coresidence. Despite much scholarly attention to this phenomenon in recent decades (for a review, see Mazurik et al, 2020), we still know relatively little about how the qualitative experience of coresidence varies across social class (van Stee, 2022). Addressing this gap, the present study revealed dramatic differences in young adults' family roles and learning environments.…”
Section: Implications For Inequality During the Covid-19 Pandemicmentioning
confidence: 65%
“…A substantial body of research illuminates class disparities in myriad dimensions of the undergraduate experience, including extracurricular involvement (Stuber, 2011), social integration (Armstrong & Hamilton, 2015), and the college-to-work transition (Roksa & Silver, 2019). Such research foregrounds parents' unequal financial resources (Rauscher, 2016) and cultural knowledge (Hamilton et al, 2018), suggesting that higher-SES parents' class resources facilitate greater educational and professional attainment (Armstrong & Hamilton, 2015;Hamilton & Armstrong, 2021;Roksa & Silver, 2019;van Stee, 2022).…”
Section: Parents' Roles In Higher Educationmentioning
confidence: 99%
“…Building on the life course framework, especially the notion of “linked lives” (Carr, 2018), we adjust for characteristics of the adult child, mother, and father within our models as each person's life experiences and background likely contributes to the overall risk of estrangement from the child's perspective. First, in line with insights from both intergenerational solidarity–conflict and life course perspectives, adult children's life course patterns, and events are associated with relationship quality and patterns of coresidence with parents (Ma & Wen, 2016; Stee, 2022), thus, these factors likely play a role in the prevalence and timing of estrangement. Adult children who are married typically have lower levels of intergenerational solidarity than those who are unmarried (Bucx et al, 2012; Swartz et al, 2011; Ward et al, 2014), in part because marriage is a “greedy institution” that takes time and resources away from other social ties (Sarkisian & Gerstel, 2008).…”
Section: Introductionmentioning
confidence: 90%
“…Further, an adult child's higher educational attainment and full‐time employment status may be associated with increased estrangement, as higher socioeconomic status may reduce the financial reasons to maintain the tie given that children no longer need financial help from parents (Swartz et al, 2011). Alternatively, higher socioeconomic achievement of the adult child may suggest lower odds of estrangement as more financial resources have been shown to reduce relational conflict and tension (Stee, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation